Penerapan Hukum Progresif dalam Penyelesaian Konflik Agraria - Setiyo Utomo (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2020)
This article aims to analyse ongoing agrarian conflicts by providing recommendations in a progressive legal paradigm approach so that people's rights can be protected. This study uses a normative juridical approach by conducting several comparative analyses of the case approach and the comparative approach of various unresolved agrarian disputes. The main finding of this research is the explosion of increasingly widespread agrarian conflicts until unresolved agrarian conflicts. Settlement of agrarian conflict disputes can be resolved if the law works as its purposes. Hence, the main point of understanding the resolution of agrarian conflicts is people awareness toward access or land ownership of as the fundamental right of every human being, which the State must fulfil according to the mandate of the constitution. The application of progressive law is expected to help resolving agrarian conflicts that prioritize human rights by considering environmental aspects to improve the people welfare through land ownership.